Supergirl : being super - Tamaki, Mariko (DC Comics, 2020)
When an earthquake shatters Midvale, uncovering secrets sixteen-year-old Kara Danvers thought would stay buried forever, she must choose between blending in and embracing her differences to save her hometown.--